2017
DOI: 10.12973/eurasia.2017.00969a
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Service Quality in Education: Views of Principals and Teachers

Abstract: The aim of this research was to take the opinions of teachers and principals to determine the ways to improve the quality of service in high schools in order to improve student satisfaction. This study tried to increase the awareness of teachers and principals about the quality in education and to provide their contribution to creating quality culture in high schools. In this study, a purposive sampling method was employed. Semi-structured interviews were conducted with 22 teachers lecturing at high schools an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
6
0
2
Order By: Relevance
“…Kepala Madrasah punya peran strategis untuk mengembangkan dan meningkatkan kompetensi guru dalam menghadapi pembelajaran di era millenial, khususnya dalam memperlancar bahasa asing dan menggunakan teknologi dalam pendidikan (Senol & Dagli, 2017). Hal yang paling mendasar diperlukan TQM adalah agar lembaga pendidikan mendapatkan kualitas terbaik dan memiliki lulusan yang mampu bersaing dan menjadi juara di tengah persaingan yang ketat.…”
Section: Pendahuluanunclassified
“…Kepala Madrasah punya peran strategis untuk mengembangkan dan meningkatkan kompetensi guru dalam menghadapi pembelajaran di era millenial, khususnya dalam memperlancar bahasa asing dan menggunakan teknologi dalam pendidikan (Senol & Dagli, 2017). Hal yang paling mendasar diperlukan TQM adalah agar lembaga pendidikan mendapatkan kualitas terbaik dan memiliki lulusan yang mampu bersaing dan menjadi juara di tengah persaingan yang ketat.…”
Section: Pendahuluanunclassified
“…Yang kedua yaitu peran pendidikan dalam meningkatkan nilai-nilai dan sikap tanggung jawab sebagai warga negara dan memelihara perkembangan kreatif dan emosional. Demirtaş, Z., & Kahveci, G. pada Senol (2017) menyampaikan bahwa guru akan mencapai kesuksesannya yang tinggi bilamana mereka dapat memenuhi apa yang dibutuhkan oleh masyarakat bahkan melebihi dari harapannya yaitu merubah kemapuan pengetahuan, keterampilan serta sikap siswa. Hoy, Jardine and Wood (2005) berpendapat bahwa istilah mutu dalam pendidikan adalah evaluasi proses mendidik dalam meningkatkan kebutuhan untuk mencapai dan mengembangkan proses bakat peserta didik dan sesuai dengan kebutuhan masyarakat.…”
Section: Kajian Teoritis Peran Kepala Sekolah Dalam Mutu Layanan Akademikunclassified
“…The results also showed that clarifying the basic elements of Hoshin Kanri methodology motivates companies to use it as an effective way to enhance the level of quality culture. (Senol & Dagli 2017), in Turkey, aimed to identify the quality of services provided to secondary school students from principals and teachers perceptions. The sample of the study consisted of (10) principals and (22) secondary school teachers.…”
Section: Previous Literaturementioning
confidence: 99%